Wybrane wskaźniki efektywności udostępniania zasobów drukowanych w polskich bibliotekach naukowych - Górny, Mirosław; Jazdon, Artur; Nowak, Piotr (Instytut Lingwistyki Uniwersytetu im. A. Mickiewicza, 1997)
The paper includes the results of a poll rating the number and utilization of printed resources in Polish scientific libraries. The results, which have been presented by field groups (i.e.. chemical, biological, technical libraries, e tc . etc.) as well as by function groups (specialist and academic libraries), concern the number of resources including both books and journals. The authors provide the number o f foreign language collections and English language collections making a clear distinction between these two categories. The figures illustrating the annual increase of these sources have also been supplied. In addition, the article offers some data concerning the following problems: range of collecting materials which have been ordered at the readers' request, time of preparing new collections for use. number o f loans, number of orders that did not take effect, collection utilization rating, number of interlibrary loans as well as the extent of selecting collections. Finally, the poll reveals information on the number of libraries researching the readers’ needs, number of libraries offering their collections for use on Saturdays and Sundays, and number of libraries which provide special loan opportunities (e.g.. weekend loans).